2022
DOI: 10.3168/jds.2021-21663
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning classification of breeding protocol descriptions from Canadian Holsteins

Abstract: Dairy farmers are motivated to ensure cows become pregnant in an optimal and timely manner. Although timed artificial insemination (TAI) is a successful management tool in dairy cattle, it masks an animal's innate fertility performance, likely reducing the accuracy of genetic evaluations for fertility traits. Therefore, separating fertility traits based on the recorded management technique involved in the breeding process or adding the breeding protocol as an effect to the model can be viable approaches to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Here, metrics such as OA (presented in Equation ( 1)) and the F1-score (presented in Equation ( 2)) are used to evaluate the classification. The OA is the ratio of test points correctly classified to all test points, and the F1-score can be viewed as a weighted average of the precision and recall of the model, which takes into account both the precision and recall of the classification model [59,60]. By comparing the real category of the samples with the model's predicted results, the results can be classified into the following four cases: true positive (TP), where the predicted value of weeds is consistent with the real value; false positive (FP), where the actual situation is the non-weeds but is incorrectly predicted as weeds; false negative (FN), where the predicted value of non-weeds is consistent with the real value; true negative (TN), where the actual situation is the weeds but is incorrectly predicted as non-weeds.…”
Section: Accuracy Evaluation Indexmentioning
confidence: 99%
“…Here, metrics such as OA (presented in Equation ( 1)) and the F1-score (presented in Equation ( 2)) are used to evaluate the classification. The OA is the ratio of test points correctly classified to all test points, and the F1-score can be viewed as a weighted average of the precision and recall of the model, which takes into account both the precision and recall of the classification model [59,60]. By comparing the real category of the samples with the model's predicted results, the results can be classified into the following four cases: true positive (TP), where the predicted value of weeds is consistent with the real value; false positive (FP), where the actual situation is the non-weeds but is incorrectly predicted as weeds; false negative (FN), where the predicted value of non-weeds is consistent with the real value; true negative (TN), where the actual situation is the weeds but is incorrectly predicted as non-weeds.…”
Section: Accuracy Evaluation Indexmentioning
confidence: 99%
“…However, this flexibility can lead to different codes indicating the same condition or protocols (Kelton et al 1998;Wenz and Giebel 2012;Lynch et al 2021). Awareness that these different codes are used in on-farm recording is important as this may require machine learning methods to combine codes or may otherwise influence genetic evaluations as demon-strated for fertility traits (Lynch et al 2021;Alcantara et al 2022). Gonzalez-Peña et al (2019) similarly reported the need to combine "RESP" and "PNEU" records for genetic evaluations of calf wellness traits in the United States.…”
Section: Recording Of Calf Diseasesmentioning
confidence: 99%